Basic processes as foundations of cognitive impairment in adult ADHD - Butzbach, Marah; Weisbrod, Matthias (Journal of neural transmission, 2019)
Attention deficit hyperactivity disorder (ADHD) in adulthood is associated with impairment of multiple aspects of cognition which adversely affect the individual’s everyday functioning. However, little is known about how these impairments are intertwined. This study explores whether impairments in basic processes (processing speed and distractibility) in adults with ADHD explain impairments in higher order functions, namely executive functions, memory, and complex attention. Furthermore, it is explored whether pharmacological treatment with methylphenidate (MPH) affects basic processes and higher order functions. A between-subjects design compared patients with ADHD without stimulant drug treatment (N = 55) and patients with ADHD treated with MPH (N = 31) with a healthy control group (N = 80). A neuropsychological test battery assessing basic processes and higher order functions was administered. Hierarchical logistic regression analyses were performed to evaluate the contribution of basic processes to impairments in higher order functions. Patients with ADHD not treated with MPH showed impairments in basic processes and higher order functions compared to controls. The impairments in basic processes explained 41-43% of impairments in executive functions, 27-29% in memory, and 56-74% in complex attention. In patients with ADHD treated with MPH, basic processes were not impaired and did not contribute significantly to impairments of higher order functions. Basic processes may constitute part of the foundation of cognitive impairments in adult ADHD. MPH may improve cognitive performance, presumably through improving basic processes. Applying this information could optimize neuropsychological assessments and inform treatment strategies by targeting basic processes.